Causes of Changing Inequality in the World - James K. Galbraith (Intereconomics, 2016)
To come up with a theory that explains inequality and that has common application across many countries, we need measurements of inequality across countries and through time that are reasonably comprehensive and reasonably reliable — and this is a major challenge. For most countries in the world today, growth reduces inequality, and rich countries are more egalitarian than poor ones. However, there are exceptions. While global financial forces and changing financial conditions have played a powerful role affecting economic inequalities, there does not appear to be a single permanent trend to inequality.
Keywords: 330; Einkommensverteilung; Konzentrationsmaß